Availability Evaluation and Maintenance Policy of Data Center Infrastructure - Camboim, Kádna; Melo, Carlos; Araujo, Jean; Alencar, Fernanda (Anais Estendidos do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2020)
The convergence of communication networks and the demand for storage and processing capacities for large amounts of information, especially in recent years, has driven requests for everything-as-a-service and has been generating, on an increasing scale, demands for new data center constructions. However, to meet dependability attributes, the design of these infrastructures needs to consider, at least, the system’s availability to be achieved. In this paper, we evaluate the availability of a Tier 1 data center infrastructure, considering the use of blade systems. We use modeling techniques based on reliability block diagrams and stochastic Petri nets to simulate a maintenance policy encompassed at different service levels (SLA). The results show dependability metrics, focusing on the availability and maintenance of these networks. We highlight the most severe difficulties in achieving high availability when there is no component redundancy, and the intervals between maintenance are long.